Efektivitas Pelaksanaan Diversi pada Anak Berhadapan Hukum dalam Tindak Pidana Pencurian dengan Pemberatan: Studi Kasus Surabaya Children Crisis Center - Ali Fuad Hasyim (Jurnal Hukum dan Sosial Politik, 2025)
This research discusses the effectiveness of the implementation of diversion for children in conflict with the law in the crime of aggravated theft, with a case study at the Surabaya Children Crisis Center (SCCC). The background of the research is based on the importance of protecting children's rights in the criminal justice sistem, in accordance with Law Number 11 of 2012 concerning the Child Criminal Justice Sistem (UU SPPA), which prioritizes restorative justice and the principle of diversion to avoid the negative impact of formal punishment on children. This research uses empirical juridical method with descriptive analysis approach, examining primary data from interviews with legal counsel at SCCC as well as secondary data from related legal literature. The results show that diversion at SCCC has been implemented according to procedures at various stages of the legal process, from investigation, investigation, to trial. However, the implementation still faces obstacles such as the lack of understanding of law enforcement officials, limited human resources at legal aid institutions, and challenges in mediation between offenders and victims. In conclusion, although the implementation of diversion in SCCC is quite effective in protecting children's rights and preventing social stigma, the implementation of diversion in SCCC is not yet effective.